Distribution, diversity, endemism, and ecology of Nymphalid butterflies (Lepidoptera: Nymphalidae) in the Loxicha Region, Oaxaca, Mexico - Rivera-Gallego, Iván Darío (2022)
Introduction: An economic activity that has boomed in the last decade in Colombian highlands is the afforestation of anthropized savannas, but its role in the conservation of fruit-feeding butterflies of gallery forests within forest cores is unknown. Objective: To compare the diversity of fruit-feeding butterflies in eucalyptus plantations and gallery forests, and the role of environmental variables. Methods: We used Van Someren-Rydon traps, two replicates of four traps, on each of four habitats sampled simultaneously from December 2020 to July 2021: four-year-old eucalyptus plantation; six-year-old eucalyptus plantation; dry soil gallery forest and waterlogged gallery forest. We also recorded ten abiotic, structural, food and habitat variables. Results: We collected 227 specimens of fruit-feeding butterflies (30 species, 23 genera, and 5 subfamilies within the family Nymphalidae). There were more species in the forests. The butterfly species varied over 50 % between the habitats; Satyrinae were more diverse in plantations. Conclusion: Afforestation in this area provides habitats for some species of fruit-feeding butterflies from adjacent natural forest remnants. Afforestations represent an intermediate disturbance scenario between the two dominant landscape units in the region.